SYNTHESIS OF NOVEL LEAD-MOLYBDENUM AND LEAD-TUNGSTEN OXYHALIDES WITH THE PINALITE STRUCTURE, PB3MOO5CL2 AND PB3WO5BR2 - Charkin D.O.; Lightfoot P. (My University, 2006)
Two new quaternary lead oxyhalides, Pb3MoO5Cl2 and Pb3WO5Br2, have been prepared. They are isostructural with the mineral pinalite, Pb3WO5Cl2, and its barium analog. The crystal structure of Pb3MoO5Cl2, has been refined from powder neutron diffraction data to Rp = 0.0564 and Rwp = 0.0342. All these structures contain significantly stretched MO5 (M = Mo, W) square pyramids incorporated into the [Pb2O2] sheets. Bond valence sums indicate significant overbonding of one of the metal sites, which increases along with structural distortions when passing from Pb3MoO5Cl2 to Pb3WO5Cl2 and from Pb3WO5Cl2 to Ba3WO5Cl2. Possibilities of preparing isostructural and structurally related compounds are discussed.
Keywords: CRYSTAL STRUCTURE; NEUTRON DIFFRACTION; PB3MOO5CL2; PINALITE; Quaternary; Cenozoic::Quaternary